Engineering mathematics - Bird, John. (Oxford : Newnes, 2003)
Engineering Mathematics is a comprehensive textbook for vocational courses and foundation modules at degree level. John Bird's approach, based on numerous worked examples supported by problems, is ideal for students of a wide range of abilities, and can be worked through at the student's own pace. Theory is kept to a minimum, placing a firm emphasis on problem-solving skills, and making this a thoroughly practical introduction to the core mathematics needed for engineering studies and practice. The book presents a logical topic progression, rather than following the structure of a particular syllabus. However, coverage has been carefully matched to the two mathematics units within the new BTEC National specifications, and AVCE specifications. New sections on Boolean algebra, logic circuits matrices and determinants have been added to ensure full syllabus match. Includes: 900 worked examples, 1700 further problems, 234 multiple choice questions (answers provided), and 16 assessment papers - ideal for use as tests or homework.
Includes index.
Keywords: Engineering mathematics; Electronic books